Can the Social Sciences Learn from the Army Program? - Thomas, Lawrence G. (Journal of Higher Education, 1946)
The article presents the lessons learned from the army training program in social science and how this affect the teaching of social sciences and humanities at Stanford University, where instructors for the army training program came from. The Army Specialized training Program (ASTP) authorized a college training called Area and Language program for enlisted men while the officers were given the Civil Affairs Training Schools (CATS) for them to perform practical jobs in winning the war. Instructors from different social science disciplines were hired to create an integrated course for the needs of students in military service. They learned that a systematic study of foreign areas led to a better grasp of the subject matter and that a panel system rather than the lecture series is more effective. For the author, the lesson is being able to identify the purpose based on the jobs to do and the problems to solve.